Regional investment standard as a tool for increasing the effectiveness of investment project implementation - Ye. T. Nadyrgaliev (Вестник университета, 2025)
This article discusses the need to create favourable conditions for investment, especially in the industrial production sector, as a critical element in reducing territorial inequality and raising the standard of living in the country. In the context of economic sanctions and limited financial capabilities of companies, achieving technological and product sovereignty is impossible without a significant increase in the investment in production. The main objective of the study is to develop a methodology for assessing the effectiveness of the regional investment standard (herein-after referred to as RIS) and its impact on the growth of the industrial production and profitability of companies. The article proposes two key tools: coefficient of investment impact on the industrial production and coefficient of investment profitability. A correlation analysis has also been conducted which, although demonstrating a low degree of dependence between the magnitude of the RIS implementation and performance indicators, points to future improvement in dynamics as investment procedures are improved. The conclusion notes that the correct methodology and its use can significantly increase the level of investment projects and stimulate economic growth in the regions. The study is based on the data of the Federal State Statistics Service on the investments in non-financial assets.